2011
DOI: 10.1093/jb/mvr085
|View full text |Cite
|
Sign up to set email alerts
|

A unique epidermal mucus lectin identified from catfish (Silurus asotus): first evidence of intelectin in fish skin slime

Abstract: The present study reports a new type of skin mucus lectin found in catfish Silurus asotus. The lectin exhibited calcium-dependent mannose-binding activity. When mannose eluate from chromatography with mannose-conjugated agarose was analysed by SDS-PAGE, the lectin appeared as a single 35-kDa band. Gel filtration showed that the lectin forms monomers and dimers. A 1216-bp cDNA sequence obtained by RACE-PCR from the skin encoded a 308 amino acid secretory protein with homology to mammalian and fish intelectins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The environmental pH and calcium concentration may influence susceptibility of fish to infection, affecting both the host (33,34) and pathogen (35). Furthermore, these levels may differ between different growth and assay buffer media used for in vitro studies.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental pH and calcium concentration may influence susceptibility of fish to infection, affecting both the host (33,34) and pathogen (35). Furthermore, these levels may differ between different growth and assay buffer media used for in vitro studies.…”
Section: Resultsmentioning
confidence: 99%
“…It may also give innate immunity against infectious pathogens28 like the epidermal slime of the more evolved fishes2930. Soapfish31 and boxfish32 slime evolved into a toxic form presumably to deter predators.…”
Section: Discussionmentioning
confidence: 99%
“…A new type of skin mucus lectin was recently found in catfish (Silurus asotus), and it was the first evidence of a fish intelectin protein [202]. Reverse transcription polymerase chain reaction (RT-PCR) demonstrated that the lectin gene was expressed in the skin (as well as in gill and kidney) and more concretely in skin and gill club cells.…”
Section: Lectinsmentioning
confidence: 99%